REVIEW: TIBETAN ENVIRONMENTALISTS IN CHINA - Reviewed by, Bill Bleisch (Asian Highlands Perspectives, 2018)
Liu Jianqiang (Ian Rowen, Cyrus K Hui, and Emily T Yeh, translators) 2015. Tibetan Environmentalists in China: The King of Dzi. Lanham, Boulder, New York, London: Lexington Books. xxi + 327 pp, index. ISBN 978-0-7391-9973-2 (hardback 105USD) - ISBN 978-0-7391-9974-9 (electronic 103.35USD). This translation is an edited and updated version of Sky Beads - Tibetan Legends by Chinese journalist Liu Jianqiang, an accomplished investigative reporter (Fowler and Dean 2006; Shapiro 2016:126). The author began work on the book in 2006 when he was a visiting scholar at Peking University. He subsequently conducted a series of lengthy in-depth interviews with several remarkable individuals from various regions of Tibet - Tashi Dorje Hashi (Tador); Rukai Karma Samdrup (Karma) and his older brother, Rinchen Samdrup (Rinchen); Tsewang Gendun Denba (Gendun), Musuo Lobsang Tsundru (Musuo), and others. What may have begun for the author as an investigation of local Tibetan environmental activism soon became something very different and more interesting: an exploration of the "remarkable lives" of individuals who had chosen to play a vibrant part in shaping the present and future of their home. The book explores not only their activities and thoughts on environmental and cultural conservation, but how these were shaped by their pasts and their current beliefs. The narrative digs unabashedly into all aspects of their lives, successes and mistakes, commitments and doubts. There is even an entire chapter devoted to the most intimate details of their complicated love lives, remarkable for the honesty and openness of the interviews.